Secular and Religious Feminisms: A Future of Disconnection?. (May 2013) - Llewellyn, Dawn; Trzebiatowska, Marta
This article identifies a disciplinary disconnection between secular and religious feminisms. While areas of study such as women's, gender and feminist studies, and disciplines like feminist studies in religion, spirituality and theology advance understanding of gender relations, they are forms of analysis that rarely keep company. As we argue, there is a disconnection grounded in a sacred/secular divide (Magee, 1999) evident through the different stages of the women's movement and feminist history. Not only is this disciplinary disconnection mutually unhelpful, but it has implications for the ways gendered religious and secular discourses operate in the public square and therefore, has implications for the future of feminist theology. This article first identifies the lack of relationship between secular and religious feminisms illustrated in three interrelated ways: secular feminisms' neglect of women's religious experiences; feminist religious studies' reservedness; and the sacred/secular binary operating in the academy. We then suggest this disconnection extends to the most recent expressions of feminism – the third wave. This article then discusses what both disciplines lose from a lack of dialogue and what might be gained by a closer relationship; particularly when contemporary events in the public sphere (such as the Pussy Riots) highlight the importance of paying attention to the way women's experiences, and secular and religious discourses interact.